Place Identity translating into Culture: the town of Rajapur in the cultural region of Konkan - Prachitee Naik; Vishakha Kawathekar (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This paper deals in defining the place identity of cultural town of Rajapur, located in the Konkan region. Rajapur is the valley situated at the confluence of the 'Arjuna' and ‘Godi’ river. Artistic temples, attractive mosques, Peshwa period structures at Jawahar Chowk and Varchi Peth are all adorning the town. The settlements of Rajapur that are the subject of this study have historical and cultural values with structures of regional culture, natural patterns, and traditions. Today, some parts of these settlements are totally neglected due to changing lifestyles, socio-economic conditions, and approaches towards rural areas. Paradoxically, Konkan is known for the coast and is the main magnet for a day’s tourist destination. The heritage is losing its identity due to unsustainable tourism, development pressure, social, economic and political issues. However, Rajapur consists rich history, cultural background, traditional housing, geology, and other factors that make it an important town in South Konkan.